Comparison of skeletal stability after sagittal split ramus osteotomy with and without extraction of the third molar in patients with mandibular prognathism. Issue 7 (September 2015) - Moroi, Akinori; Yoshizawa, Kunio; Iguchi, Ran; Hiroumi, Ikawa; Kosaka, Akihiko; Hotta, Asami; Tsutsui, Takamitsu; Saita, Yuriko; Ueki, Koichiro
Abstract Purpose The purpose of this study was to evaluate, through cephalometric analysis, the skeletal stability following BSSRO performed with and without extraction of the third molar, and to examine the healing of the extraction sockets through computed tomography (CT). Patients and methods Sixty Japanese patients (male: 14, female: 46) diagnosed with mandibular prognathism were included in this study. While 30 patients underwent BSSRO along with extraction of the third molar (extraction group), the other 30 patients underwent BSSRO alone (non-extraction group). Skeletal stability was assessed using axial, frontal, and lateral cephalograms. CT scans were obtained 1 week after surgery and at the 1-year follow-up for all the patients. CT value was measured at the point of the extraction socket on the horizontal plane parallel to the Frankfurt plane using computer software (SimPlant 2011; Materialise Dental, Leuven, Belgium). The region of interest (ROI) was approximately 4 mm2 and the mean value was recorded. Healing of the extraction sockets was examined through CT 1 year postoperatively. Results There were no significant differences between the groups for any of the parameters at any observation interval. In the extraction group, there were significant differences between the values of CT obtained 1 week postoperatively and 1 year postoperatively in the extraction socket (P = 0.0003). Conclusion The results of this study indicate that there is no significant difference in the skeletal stability between BSSRO performed with and without third molar extraction.